Segregation Analysis of Transgenic Rice Plants cv Rojolele Harboring cry1B Gene and Plant Selection for Potential to Yellow Stem Borer - Estiati, Amy; Sulistyowati, Yuli; Zahra, Fatimah; Nurhasanah, Ade Nena; Rachmawati, Syamsidah; Loedin, Inez Hortenza Slamet (BRIN, 2012)
Transgenic rice plants harboring resistant gene to yellow stem borer, cry1B gene had been obtained. However, the cry1B gene in second generation of transgenic rice lines still segregating following Mendelian ratio 3:1. For further use in the breeding programs, it is important to ensure that the gene is dominant gene and the plants are homozygous for cry1B gene. Selection of homozygous transgenic rice lines containing cry1B gene at third, fourth and fifth generation had been conducted by PCR. The presence of cry1B gene was determined by showing the PCR product of 1.9 kb. Segregation analysis proved that six transgenic rice lines i.e. 3R7.8.15.1, 3R7.8.15.9, 3R7.8.15.10, 3R7.8.15.15, 3R7.8.15.21, 3R7.8.15.29 are homozygous lines for cry1B gene. Moreover, bioassay studies at vegetative stage on six homozygous transgenic rice lines showed that these transgenic rice lines are potential resistant to yellow stem borer comparing with non-transgenic plants, with the score of 0 (indicated no symptom) for six transgenic lines and score of 9 (more than 60% damaged tillers ) for non-transgenic plants. However, to confirm the efficacy of cry1B gene to yellow stem borer in natural condition, confined field trial in endemic area of yellow stem borer should be conducted.